Aβ40 modulates GABAA receptor α6 subunit expression and rat cerebellar granule neuron maturation through the ERK/mTOR pathway. (24th October 2013) - Zhan, Xiao‐Qin; Yao, Jin‐Jing; Liu, Dong‐Dong; Ma, Qianqian; Mei, Yan‐Ai
Abstract In addition to their neurotoxic role in Alzheimer's disease (AD), β‐amyloid peptides (Aβs) are also known to play physiological roles. Here, we show that recombinant Aβ40 significantly increased the outward current of the GABAA receptor containing (GABAAα6) in rat cerebellar granule neurons (CGNs). The Aβ40‐mediated increase in GABAAα6 current was mediated by an increase in GABAAα6 protein expression at the translational rather than the transcriptional level. The exposure of CGNs to Aβ40 markedly induced the phosphorylation of ERK (pERK) and mammalian target of rapamycin (pmTOR). The increase in GABAAα6 current and expression was attenuated by specific inhibitors of ERK or mTOR, suggesting that the ERK and mTOR signaling pathways are required for the effect of Aβ40 on GABAAα6 current and expression in CGNs. A pharmacological blockade of the p75 neurotrophin receptor (p75NTR), but not the insulin or α7‐nAChR receptors, abrogated the effect of Aβ40 on GABAAα6 protein expression and current. Furthermore, the expression of GABAAα6 was lower in CGNs from APP−/− mice than in CGNs from wild‐type mice. Moreover, the internal granule layer (IGL) in APP−/− mice was thinner than the IGL in wild‐type mice. The injection of Aβ40 into the cerebellum reversed this effect, and the application of p75NTR blocking antibody abolished the effects of Aβ40 on cerebellum morphology in APP−/− mice. Our results suggest that low concentrations of Aβ40 play a role in regulating CGN maturation through p75NTR. <boxed-text content-type="graphic" id="jnc12471-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> In addition to its neurotoxic role in Alzheimer's disease, Aβ is known to play important physiological roles. Whether Aβ improves neuronal development and maturation remains elusive. Our results demonstrate that low concentrations of Aβ40 significantly increase the GABAA receptor α6 subunit expression and associated current in cerebellar granule neurons (CGNs) via the p75NTR and MEK/ERK pathway. Aβ also increases the thickness of the internal granule layer in APP−/− mice cerebellum. Our data provide new evidence for the role of Aβ40 in regulating the maturation of CGNs.